Effect of alkaloid and phenolic extract administration oi Allium cepa L Ù on some biochemical parameters of blood on albino mice (Baghdad Science Journal, 2004)
؛ ١٨his study male and female albino mice werdministr^d doses of alkaloid and phenolic extracts of Allium cepa at doses of( 25 ,50,100, 200) mg / kg of( body weight). males and females were divided into four groups and each croup comprised mice were injected intra^ritonially daily for one week and orally ٢٠٢ one month . After which animals were killed and the serum was separated for biochemical analysis (total blood suger, total protein , otal cholesterol). Results showed significant decrease ( p< 0,05) in the total blood suger and total cholesterol on the serum of both males and females and significant increase( p< 0,05) in the total serum protein of both males and females of the two types of injection and oral administration and by both Alkaloid and phenolic extracts . However it was found that the alkaloid extract was more effective than phenolic extract.